If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2(7x + -13) = -162 Reorder the terms: 3x + 2(-13 + 7x) = -162 3x + (-13 * 2 + 7x * 2) = -162 3x + (-26 + 14x) = -162 Reorder the terms: -26 + 3x + 14x = -162 Combine like terms: 3x + 14x = 17x -26 + 17x = -162 Solving -26 + 17x = -162 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '26' to each side of the equation. -26 + 26 + 17x = -162 + 26 Combine like terms: -26 + 26 = 0 0 + 17x = -162 + 26 17x = -162 + 26 Combine like terms: -162 + 26 = -136 17x = -136 Divide each side by '17'. x = -8 Simplifying x = -8
| 240=-7x-3(4x-23) | | 7x^2+xy+y^2=9 | | 2x+5y=29 | | 5x-4(7x+23)=184 | | 5x-(7-2x)=8x+9 | | 2y-8=30 | | 2u-8=30 | | -69=6x-3(-3x-7) | | 390.75=x | | -3x-6(4x-18)=297 | | f(c)=c^2+8c+12 | | -3x-5(-x-16)=68 | | -3(x+8)+4(x+9)=2x | | 14+6M-2-3M=5M+8 | | 5x^2-10x+6y^2+36y+60=0 | | 5w^2=35w | | 12m-2m+3+4m=31 | | 12-2m+3+4m=31 | | 9v^2+9v-40=0 | | 6+8m+8=12m+2+4 | | 6+8m=12m+2+4 | | 8(m+4)(2m-1)= | | 9x+4x=0.9-1.4 | | 3M+15=5m+9 | | 5M+40=100 | | 100=5M+40 | | 151=7x-6(-3x+4) | | 2x-3.4=x-3.6 | | 2xy=x^6+y^6 | | 57.6=240(0.03)t | | 3x-13+4x-24=180 | | 1half(6x-8)=41 |